Integrating insecticidal and repellency properties against American cockcroaches (Periplaneta americana) to non-load bearing concrete masonry unit - Acuña, Anna Tricia L. (2015)
The study aimed to formulate and assess a standard design of concrete masonry unit with integrated cockroach insecticide and repellent properties derived from organic and inorganic materials using standard tests for non-load bearing concrete masonry units and through controlled experimentations. The study also aimed to identify the optimum ratio and proportion of the raw materials to create an efficient cockroach repellent and insecticidal non-load bearing concrete masonry unit. Pandan, lemongrass, cucumber peelings, and diatomaceous earth were utilized in this study which contain insecticidal and repellent properties against American cockroaches (Periplaneta americana), an urban pest. The study comprised two main parts, the material development phase wherein 6 formulations were made: 1.) Formulation A ? Ratio by volume 1 cement : 2 Diatomaceous earth 2.) Formulation B ? Ratio by volume 1 cement : 2 fine sand 3.) Formulation C ? Ratio by volume 1 cement : 4 Diatomaceous earth 4.) Formulation D ? 5% Cucumber peels, 65% fine sand, 30% Portland cement 5.) Formulation E ? 5% Pandan leaves, 65% fine sand, 30% Portland cement 6.) Formulation F ? 5% Lemongrass, 65% fine sand, 30% Portland cement The second phase of the study comprised the insecticidal and repellency property testing of the produced formulation against the American cockroach specimens which ran for 30 days. The results for the insecticidal and repellency testing were analyzed using the t-Test and Attractancy and Repellency formula (Leonard and Ehrman, 1977). After the comparison of results, the study concluded that the Formulation E (5% pandan, 65% fine sand, 30% Portland cement) result was the only significant t-value at p=0.05. The t-value calculated at 0.001 implies that the insecticidal result gathered from the Formulation E (5% pandan, 65% fine sand, 30% Portland cement) experiment was of very high significance; Deeming the pandan plant as the most favorable additive to the produced masonry unit. The limitations of the study include the insufficiency of equipment and supply of cockroach specimens, time constraints and the setting of experimentation. Diminishing these limitations is recommended. An in-depth research and experimentation is recommended to supplement the conducted study. Lastly, it is recommended to have additional tests for Diatomaceous earth and Pandan as organic additives in various formulations; with the additives in various amounts. This will be able to determine what is the most viable formulation for the developed concrete masonry unit with insecticidal and repellency properties.